An Electrostatic Method for Manufacturing Liquid Marbles and Particle-Stabilized Aggregates - Ireland, Peter M.; Thomas, Casey A.; Lobel, Benjamin T.; Webber, Grant B.; Fujii, Syuji; Wanless, Erica J. (Frontiers in Chemistry, 2018)
We have developed a method for transferring particles from a powder bed to a liquid droplet using an electric field. This process has been used to create liquid marbles with characteristics not normally found in those formed by direct contact methods such as rolling. It has also been used to manufacture hydrophilic particle-liquid aggregates and more complex layered aggregates incorporating both hydrophobic and hydrophilic particles. This article briefly outlines the electrostatic aggregation method itself, the materials used and structures formed thus far, and explores the rich fundamental physics and chemistry underpinning the process as they are understood at present.